1993
DOI: 10.2527/1993.711185x
|View full text |Cite
|
Sign up to set email alerts
|

Administration of GnRH at estrus influences pregnancy rates, serum concentrations of LH, FSH, estradiol-17 beta, pregnancy-specific protein B, and progesterone, proportion of luteal cell types, and in vitro production of progesterone in dairy cows

Abstract: Four experiments were conducted to examine effects of GnRH administered at estrus on various reproductive characteristics in repeat-breeding dairy cows (eligible for third service). In Exp. 1, cows (n = 8 per group) received (i.m.) either saline or 50, 100, or 250 micrograms of GnRH at 12 h after onset of estrus. There was a positive linear (P < .05) effect of dose on concentrations of LH, but not of FSH, in serum at 2 h after the injection. Concentrations of progesterone (P4) were higher (P = .10) through 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
2
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 0 publications
0
22
2
1
Order By: Relevance
“…Surprisingly, a large proportion (30 to 40 per cent) of the animals in the control groups had also received treatments for previous fertility-related conditions, possibly reflecting the pressure that modern dairy cows are under. Survival analysis in this study did not reveal any positive effect of fertility treatment, despite the number of studies supporting the efficacy of various drugs to treat repeat breeders (Stevenson and others 1990, Mee and others 1993, Villarroel and others 2004, Répási and others 2005, Szenci and others 2006). Indeed, treated repeat breeder animals took a considerably longer time after calving to establish a pregnancy compared with untreated animals.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Surprisingly, a large proportion (30 to 40 per cent) of the animals in the control groups had also received treatments for previous fertility-related conditions, possibly reflecting the pressure that modern dairy cows are under. Survival analysis in this study did not reveal any positive effect of fertility treatment, despite the number of studies supporting the efficacy of various drugs to treat repeat breeders (Stevenson and others 1990, Mee and others 1993, Villarroel and others 2004, Répási and others 2005, Szenci and others 2006). Indeed, treated repeat breeder animals took a considerably longer time after calving to establish a pregnancy compared with untreated animals.…”
Section: Discussioncontrasting
confidence: 64%
“…There have been many studies on pharmacological treatment for repeat breeders but success rates have been poor (Stevenson and others 1990, Mee and others 1993, Villarroel and others 2004, Répási and others 2005). Therefore a remedy involving artificial reproductive technologies may be more appropriate.…”
mentioning
confidence: 99%
“…Echternkamp (1978) administered gonadorelin to puerperal anestrous beef cows and detected a significant dose response in AUC. Also Mee et al. (1993) determined LH response to various doses of gonadorelin given immediately after artificial insemination to dairy cows, approximately 12–20 h after the spontaneous LH surge.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with buserelin increases the number of LLC and the volume of the CL present at the time of treatment (Twagiramungu et al, 1995a). Likewise, Mee et al (1993) reported an increase of the number of LLC in 10-d-old CL when Cystorelin was administered at estrus. Treatment of ewes with LH or hCG increases the number of LLC and decreases that of SLC (Niswender et al, 1985;Farin et al, 1988).…”
Section: Functional and Morphological Changes Of The Corpus Luteummentioning
confidence: 93%